(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article is devoted to the scientific and theoretical analysis of the role of civil society and its institutions in the formation of a positive image of power, the current situation in the functioning of civil society institutions in Uzbekistan. The article also describes the results of an empirical study of the activities of non-governmental non-profit organizations (NGOs), which shows a number of difficulties that require attention. In solving these difficulties, the role of NGOs in today’s society Uzbekistan will be further strengthened, and will affect the formation of a positive image of power in the minds of citizens.